ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TOTAL PENDAPATAN PENGRAJIN PADA INDUSTRI KERAJINAN PATUNG KAYU di KABUPATEN BADUNG - Friawan, Kadek Cahya; Budhi, Made Kembar Sri (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 3 (2022): VOL 11 NO 3, MARET 2022 [807-1213]DO - 10.24843/EEP.2022.v11.i03.p15, 2022)
The industrial sector an important role because development of the industrial sector increasing, which has a major impact on economic development and growth. One type of business in the industrial sector is the wood sculpture industry. The existence of wooden sculpture crafts in Badung Regency is an alternative in overcoming the increase in unemployment and is a place for craftsmen to earn income. This study aims to analyze effect of working hours, educational level, and technology simultaneously on the income of craftsmen in the wood sculpture industry in Badung Regency, to analyze the effect of working hours, education level, and technology partially on the income of craftsmen in the wood sculpture industry. Badung Regency. This research uses primary data. Retrieval of data through non-behavioral observation, structured interviews, and questionnaires. The data analysis technique used multiple linear regression analysis techniques. According to the analysis found that 1) variables on the income of craftsmen in the wood sculpture industry in Badung Regency, 2) variables working hours, education level, and technology partially have a positive effect on the craftsmen's income. in the wood sculpture industry in Badung Regency. Keywords: Income, Working Hours, Education Level, Technology